Inside Cover: A Dendritic Supramolecular Complex as Uniform Hybrid Micelle with Dual Structure for Bimodal In Vivo Imaging (Chem. Eur. J. 12/2017). Issue 12 (2nd January 2017) - Zhang, Simin; Zheng, Yanmei; Yin, Shengyan; Sun, Jingzhi; Li, Bao; Wu, Lixin
Abstract : A dendritic hybrid complex bearing a polyoxometalate core that performs dual micellar structure was used as a carrier to uptake cationic fluorescent dye, forming a luminescent complex. The uniform size (5−6 nm), definite molecular weight, and precise chemical composition make the dye‐loaded complex a bimodal probe for in vivo imaging. Moreover, both in vivo fluorescence and magnetic resonance measurement further confirmed that the complex acts as a liver‐specific contrast agent for clinical diagnosis. More information can be found in the Full Paper by B. Li et al. onpage 2802 ff.